Efektivitas Pembelajaran Science Technology Engineering and Math (STEM) terhadap Hasil Belajar di Sekolah: Meta Analisis - Siregar, Winda Lestari; Syafrijon, Syafrijon; Giatman, Giatman; Ganefri, Ganefri; Krismadinata, Krismadinata; Jalinus, Nizwardi (AI Society & STMIK Indonesia, 2024)
Education at the high school (SMA) and vocational school (SMK) levels faces challenges in preparing creative and competent students. To address these challenges, a combination of technology is needed in the fields of science, mathematics, and engineering. A study on the implementation of STEM (Science, Technology, Engineering, and Mathematics) in learning in Indonesia. To test its effectiveness, a meta-analysis was conducted which included 25 articles published between 2018 and 2023. The findings showed that STEM learning has a significant role in improving student learning outcomes with an overall effect size of 6,89. Based on the data analysis of the application of the STEM approach, it can develop the ability to solve problems rationally, conduct research, question, collaborate, criticize, analyze and can also improve the ability to access information, adapt to change, make decisions, produce, be responsible, show curiosity, interact in a social and cultural context, and develop leadership and entrepreneurship traits in students. The STEM approach provides a solid foundation for developing a variety of skills and attitudes that are important in facing the challenges and demands of the modern world of students.